2006
DOI: 10.1007/s11104-005-4628-7
|View full text |Cite
|
Sign up to set email alerts
|

Can the Biochemical Features and Histology of Wheat Residues Explain their Decomposition in Soil?

Abstract: The biochemical characteristics or quality of crop residues is an important factor governing soil residue decomposition. To improve C and N biotransformation models the process underlying this decomposition needs to be better understood and new quality criteria found to describe it. The aims of this explorative study were to (i) improve our understanding of residue decomposition from detailed studies of cell wall biochemical compositions and tissue architecture (ii) find new ways of exploring generic indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 40 publications
(62 reference statements)
7
53
0
2
Order By: Relevance
“…Chemical characteristics of decomposing leaves and roots were expressed in relation to the initial dry matter (non-decomposed dry matter, ND-DM) by taking into account the loss of mass by decomposition, calculated from the cumulative amounts of mineralized C (Machinet et al 2009). These chemical analyses were performed on only two replicates at each date, as previous experiments demonstrated extremely low variation in similar results (Bertrand et al 2006;Machinet et al 2009Machinet et al , 2011a. This low number of replicates decreased the power of statistical analyses so that significant results should be viewed as conservative.…”
Section: Data Treatment and Analysismentioning
confidence: 78%
See 2 more Smart Citations
“…Chemical characteristics of decomposing leaves and roots were expressed in relation to the initial dry matter (non-decomposed dry matter, ND-DM) by taking into account the loss of mass by decomposition, calculated from the cumulative amounts of mineralized C (Machinet et al 2009). These chemical analyses were performed on only two replicates at each date, as previous experiments demonstrated extremely low variation in similar results (Bertrand et al 2006;Machinet et al 2009Machinet et al , 2011a. This low number of replicates decreased the power of statistical analyses so that significant results should be viewed as conservative.…”
Section: Data Treatment and Analysismentioning
confidence: 78%
“…It contains 16.8 % clay, 76.3 % silt and 3.8 % sand, has an organic carbon content of 8.70 mg C g -1 and a pH (soil H 2 O) of 7.6 (Bertrand et al 2006). Soil was collected in autumn 2008 from 10 soil cores to a depth of 0-30 cm, then pooled and air-dried for 2 days to reduce moisture content to 120 mg water g -1 dry soil.…”
Section: Soil Sampling and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the chemical composition of plant residues changes during decomposition in soil (Trinsoutrot et al 2000;Bertrand et al 2006); however, there are few studies addressing the water retention properties of plants during decomposition (Dresboll and Magid 2006). The water storage characteristics of crop residues are extremely important parameters for modeling the decomposition of crop residues, particularly when residues are left at the soil surface under notill conditions ).…”
mentioning
confidence: 99%
“…Studies in the rumen environment have shown that arabinose is degraded more rapidly than xylose (Åman 1985;Nordkvist and Åman 1986;Albrecht et al 1987;Jung et al 1998). However, the rate of degradation of arabinoxylans in grasses has been found to decrease with increasing degree of branching, as indicated by an increase in the arabinose-to-xylose ratio (Albrecht et al 1987;Bertrand et al 2006). On the other hand, Vailhé et al (2000) found a positive correlation between the arabinose-to-xylose ratio and degradation rate.…”
Section: Discussionmentioning
confidence: 99%